Seizures and EEG characteristics in a cohort of pediatric patients with dystroglycanopathies. (October 2022) - Yang, Haipo; Song, Danyu; Liu, Yidan; Chen, Xiaoyu; Zhu, Ying; Wei, Cuijie; Fu, Xiaona; Liu, Xiaoyan; Yang, Zhixian; Xiong, Hui
Highlights: Seizures and epilepsy were found in 15.3% of DGP patients in the current study and were mainly induced by fever. Seizures and epilepsy could occur in FCMD, MEB, CMD-MR and LGMD patients. Seizures were relatively more frequent in severe phenotypes of DGP, such as FCMD and MEB. Abnormal background activities were the most common EEG patterns, which were closely related to type II lissencephaly. Abstract: Purpose: To delineate the seizure type, phenotype and V-EEG patterns of dystroglycanopathy (DGP) and correlate them with the neuroradiological and genetic results. Methods: Patients with seizures were screened from our dystroglycanopathy database from January 2010 to March 2021. Detailed clinical information, including seizure type, brain magnetic resonance imaging (MRI), EEG and genetic analysis, was collected. Results: Thirteen patients (15.1%, 13/86) had seizures. Most patients had a severe phenotype. The mean age at first seizure onset was 2 years and 8 months. The most common seizure type was generalized tonic-clonic seizure (GTCS), with 92.3% (12/13) induced by fever. Three patients were diagnosed with epilepsy. Most patients did not take any medicine. A few patients had irregular use of antiseizure medications (ASMs). Of the 13 patients, seven patients were diagnosed with MEB, four patients with POMGNT1 mutations, two with ISPD mutations, and one with POMT1 mutation. Three patients were diagnosed with FCMD with FKTN mutations. Two patients were diagnosed with CMD-MR, one patient with ISPD mutation, and one with POMT1 mutation. One patient was diagnosed with LGMD with FKRP mutation. Nine patients underwent EEG examination, and eight patients had abnormal EEG results, including abnormal background activities in three patients, abnormal background activities combined with paroxysmal discharges in three patients, pure paroxysmal discharges in one patient and positive phase sharp waves in the occipital region in one patient. For radiology, brain MRI was available for 12 patients. The brain MRI of nine patients showed type II lissencephaly. Two patients showed cerebellar hypoplasia and brainstem hypoplasia. One patient had a normal brain MRI result. Patients with type II lissencephaly usually had abnormal background activities and paroxysmal discharges. Conclusion: The seizure phenotype of dystroglycanopathy (DGP) is characterized by GTCS, which was the most common seizure type, while focal seizures and epileptic spasms could also occur in DGP patients. Most seizures were induced by fever. Seizures were relatively more frequent in severe phenotypes of DGP, such as FCMD and MEB. Abnormal background activities were the most common EEG patterns, which were closely related to type II lissencephaly.